Valuasi Ekonomi Objek Wisata Pantai Parangtritis, Bantul Yogyakarta - Khoirudin, Rifki; Khasanah, Uswatun (Jurnal Ekonomi dan Pembangunan Indonesia, 2018)
The valuation of Pantai Parangtritis becomes very important along with the micro issue concerning the plan of infrastructure development, facilities and infrastructure in south region. Development of infrastructure in process is Jalur Lintas Selatan Street which includes the area around Parangtritis Beach. The analytical tool used to know variable that influence number of traveler to Parangtritis tourist attraction and the economic value of Parangtritis Beach is Travel Cost Method. Based on the research findings that the variable of total cost, income level, age, and education level influence the number of visits to Parangtritis Beach. While the economic valuation of Parangtritis Beach is Rp14.605.101.491.